Exploration of Education for the Development of Party Members among Ethnic Minority Students in Universities - Sun, Mingyuan (International Journal of Social Sciences and Public Administration, 2024)
It is of great significance to lay a solid foundation for the ideology of the Chinese nation community and strengthen the organizational training and development of minority students in mainland Chinese universities. Based on the cognitive thinking characteristics and cultural acceptance level of minority students, a research method combining questionnaire surveys and individual interviews was used to investi- gate the development of party members among minority students in a university in Guangdong Province. The research results reflect some objective problems: minority students have a strong will-ingness to join the party but the application rate is low, participation in party training courses is serious but the effectiveness is not satisfactory, and there is a lack of targeted training and inspection for minority student party activists. Therefore, it is necessary to further optimize the education model for minority students, improve the party member training mechanism, and cultivate more polit- ically and ideologically qualified, and professionally competent minority student party members for the further development of socialist construction and national unity and progress.